2010
DOI: 10.1021/np100201p
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Cytotoxic Activity of Withanolides from Acnistus arborescens

Abstract: Three compounds were isolated from Acnistus arborescens, a tree commonly used in South and Central America in traditional medicine against several infectious diseases, some of which are caused by fungi. Bioassay-guided fractionation of a MeOH extract of leaves, based on its anti-Pneumocystis carinii activity, led to the isolation of compounds 1-3. Mono- and bidimensional NMR analyses enabled identification of two new withanolides, (20R,22R)-5beta,6beta-epoxy-4beta,12beta,20-trihydroxy-1-oxowith-2-en-24-enolide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
2
17
0
2
Order By: Relevance
“…Comparison of salpichrolide A and salpichrolide C showed that the cleavage of the 5,6‐epoxy group to give the 5 α ,6 β ‐diol abolished the cytotoxic activity, in agreement with results previously reported in the literature . The presence of a hydroxy group at C(12) position ( α or β ) led to a loss of activity (LNCaP and T47D), this is observed when comparing the compounds salpichrolide A and salpichrolide T and compound 6 , in agreement with results previously reported for compounds with similar structural features . Finally, no loss of activity was observed when the 5 α ,6 α ‐epoxy functionality was replaced by 5 α ‐chloro‐6 β ‐hydroxy system (salpichrolide A and 1 ).…”
Section: Resultssupporting
confidence: 91%
“…Comparison of salpichrolide A and salpichrolide C showed that the cleavage of the 5,6‐epoxy group to give the 5 α ,6 β ‐diol abolished the cytotoxic activity, in agreement with results previously reported in the literature . The presence of a hydroxy group at C(12) position ( α or β ) led to a loss of activity (LNCaP and T47D), this is observed when comparing the compounds salpichrolide A and salpichrolide T and compound 6 , in agreement with results previously reported for compounds with similar structural features . Finally, no loss of activity was observed when the 5 α ,6 α ‐epoxy functionality was replaced by 5 α ‐chloro‐6 β ‐hydroxy system (salpichrolide A and 1 ).…”
Section: Resultssupporting
confidence: 91%
“…12-OH group: 12β-Hydroxywithanolide D 49 is slightly less potent than withanolide D 48 [22]. 14,15-epoxy-group: 14α,15α-Epoxywithaferin A 50 is less potent than withaferin A 1 [35].…”
Section: -Oac Groupmentioning
confidence: 97%
“…From the biogenetic origin, it is likely that type I compounds are precursors to the more advanced structural types II−XXII. Type I withanolides that display the most promising antiproliferative characteristics also contain Δ 2 -1-oxo-functionality in ring A, a 5β,6β-epoxy-group in ring B, and a nine-carbon side chain incorporating the δ-lactone functionality found in withaferin A 1 [17], withacnistin 59 [18,19], withanolide D 48 [20][21][22][23], withanolide E 36 [8,[24][25][26][27], and 4β-hydroxywithanolide E 37 (Fig. 4) [8,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, we did observe an anti‐ Pneumocystis activity for C. odorata (MIC 100 ≤ 1 µg/ml for the hydro‐ethanolic extract) and A. arborescens (MIC 100 = 100 µg/ml for hexanic extract and 10 µg/ml for ethanolic or hydro‐ethanolic extracts due to withanolides) (Roumy et al ., ).…”
Section: Resultsmentioning
confidence: 99%